Construction applicability of mechanical methods for connecting aisle in the bohai mudstone stratum with high water pressure - Zhang, Wencui; Li, Yang; Dong, Zibo; Yang, Qiye (Frontiers in Earth Science, 2023)
The construction of a mechanical connecting aisle in the Bohai mudstone stratum with high water pressure, based on the interval tunnel of Qingdao Metro Line 8, is challenging. In this study, a cutter, propulsion system, and back supporting system were designed to handle the key and difficult points and risks of the aforementioned construction. Furthermore, targeted construction schemes were adopted for sleeve sealing, sleeve removal, and improvement of sleeve sealing. The applicability of the improved mechanical construction method to the geological conditions of the Qingdao area was verified through a numerical simulation. The research results can provide a reference for the mechanical construction of connecting aisle under similar formation conditions.